Analytical solution for horizontal vibration of end-bearing single pile in radially heterogeneous saturated soil - Cui, Chunyi; Liang, Zhimeng; Xu, Chengshun; Xin, Yu; Wang, Benlong (Applied mathematical modelling, 2023)
•An analytical approach for the horizontal vibration of single pile in radially heterogeneous saturated soil is proposed.•The corresponding analytical solution is obtained by combining the potential function and variable separation methods.•The obtained solution is degenerated to validate its accuracy via independent comparisons with existing solutions.•The influence of radial heterogeneity of saturated soil on horizontal vibration characteristics of pile is investigated. Employing Biot's dynamic equations and Novak's thin-layer theory, an analytical model for the horizontal vibration of a single pile embedded in the radially heterogeneous saturated soil is established. Firstly, the frequency-domain response of surrounding soil is derived by means of the potential function, Laplace transformation and variable separation methods. Secondly, the analytical solution for the horizontal impedance of pile head is deduced by combining the conditions of the displacement continuity and stress equilibrium on the soil-pile interface. Finally, the obtained solution is degenerated to validate its accuracy via independent comparisons with different existing solutions. On this basis, the effect of soil radial heterogeneity on the horizontal vibration of an end bearing pile is further discussed by conducting an extensive parametric analysis.